2016
DOI: 10.18632/oncotarget.12845
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Enox1 in tumor stroma increases the efficacy of fractionated radiotherapy

Abstract: The goal of this investigation was to clarify the question of whether targeting Enox1 in tumor stroma would synergistically enhance the survival of tumor-bearing mice treated with fractionated radiotherapy. Enox1, a NADH oxidase, is expressed in tumor vasculature and stroma. However, it is not expressed in many tumor types, including HT-29 colorectal carcinoma cells. Pharmacological inhibition of Enox1 in endothelial cells inhibited repair of DNA double strand breaks, as measured by γH2AX and 53BP1 foci format… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…ENOX1 is a member of the ecto-nox family of NADH oxidases, which are involved in many cellular processes controlling cell growth and survival. 50 A recent study has shown that drugs targeting ENOX1 result in erroneous DNA double strand break repair, 51 That the difference in the prognosis of cancers with and without 13q deletion was relatively small (10%) even in our large set of more than 7300 analyzable cancers might explain the discrepant findings made in earlier studies employing LOH analysis to estimate the role of 13q deletions in 16-294 cancers. 24,25,27,[29][30][31][32][33]35,[37][38][39] While some studies reported higher rates of 13q loss with increased Gleason grade, 24 advanced tumor stage, 29,30,37,38 metastasis, 38 and patient outcome, 35 others could not reproduce such associations in their studies.…”
Section: Multivariate Analysesmentioning
confidence: 66%
See 1 more Smart Citation
“…ENOX1 is a member of the ecto-nox family of NADH oxidases, which are involved in many cellular processes controlling cell growth and survival. 50 A recent study has shown that drugs targeting ENOX1 result in erroneous DNA double strand break repair, 51 That the difference in the prognosis of cancers with and without 13q deletion was relatively small (10%) even in our large set of more than 7300 analyzable cancers might explain the discrepant findings made in earlier studies employing LOH analysis to estimate the role of 13q deletions in 16-294 cancers. 24,25,27,[29][30][31][32][33]35,[37][38][39] While some studies reported higher rates of 13q loss with increased Gleason grade, 24 advanced tumor stage, 29,30,37,38 metastasis, 38 and patient outcome, 35 others could not reproduce such associations in their studies.…”
Section: Multivariate Analysesmentioning
confidence: 66%
“…ENOX1 is a member of the ecto‐nox family of NADH oxidases, which are involved in many cellular processes controlling cell growth and survival . A recent study has shown that drugs targeting ENOX1 result in erroneous DNA double strand break repair, suggesting a role of ENOX1 deletion for development of genetic instability. Furthermore, it is well conceivable, that RB1 , located 4.5 megabases upstream of ENOX1 represents another relevant gene for 13q deleted prostate cancers as a co‐deletion of RB1 was seen in 98.6% of ENOX1 deleted cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, targeted inhibition of ENOX1 activity to inhibit tumor angiogenesis may be a feasible strategy for tumor control. Smith et al (2016) found that targeted inhibition of ENOX1 in tumor stroma improved radiotherapeutic efficacy in tumor patients. IGF2BP2 is a member of the insulin-like growth factor 2 mRNA-binding protein family, which are newly reported m6A "readers."…”
Section: Discussionmentioning
confidence: 99%